Assessment of the quality of online information on cataract surgery. Issue 4 (October 2018) - Logeswaran, Abison; Chong, Yu Jeat; Awad, John; Edmunds, Matthew R.
Abstract : N/A: The quality of health information of 51 unique websites on cataract surgery was assessed using 2 validated instruments, the DISCERN instrument and JAMA benchmark criteria. Quality was evaluated on a combination of different criteria such as aims, resources cited, bias, authorship, and treatment choices.